PENERAPAN MEDIA PEMBELAJARAN PIXELWAVE UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK DALAM PELAJARAN BAHASA INDONESIA KELAS V SEKOLAH DASAR - Nia Yuliani; Wendri Wiratsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Listening skills are one of the skills that must be mastered by students because this ability is the foundation of the other three language skills, namely speaking, reading, and writing. By having good listening skills, students will more easily understand the material or information presented by the teacher. From there, they can use it to develop more structured speaking and writing skills. However, in the field, many students still have low listening skills. This is caused by the use of media and learning methods that are still conventional and tend to use the lecture method, so that student engagement in the learning process is still lacking. For this reason, an interactive multimedia-based learning media called Pixelwave was developed as a supporting tool to improve students' listening skills. The type of research used in this study is R&D (Research and Development). The subjects were 25 fifth-grade elementary school students in Regency X. The results showed a significant increase in students' listening skills after using Pixelwave media compared to conventional media. From the data analysis conducted, it can be concluded that the use of Pixelwave media has proven effective in improving fifth-grade students' listening skills in Indonesian language lessons. Thus, this media can be recommended as a fun learning alternative to improve students' reading skills.